Impact of transformational leadership and school environment on organizational commitment of teachers - Jecyl C. Bantilan; Ellen Joy J. Sombilon; Analyn R. Regidor; Danilo P. Mondoyo; Ma. Melanie N. Edig (Goodwood Publishing, 2024)
Purpose: This study investigated the influence of transformational leadership and the school environment on the organizational commitment of teachers. Research methodology: A quantitative nonexperimental research design with multiple regression analysis was employed. Using the Raosoft calculator, 115 of the 162 public secondary teachers in Davao City were selected as respondents who rated the three adopted questionnaires. Results: The findings revealed a high level of transformational leadership, school environment, and teachers’ organizational commitment. In terms of significant relationships, both transformational leadership and the school environment were moderately positive and statistically significant. The results of the regression revealed that transformational leadership and the school environment are responsible for 46.2% of the variation in the organizational commitment of teachers. However, the results of the coefficients revealed that only the school environment could predict organizational commitment. Limitations: This study only involved 115 respondents and used adopted questionnaires, which might be quite different from the context of the respondents. Contribution: The results and findings of this study can be used as a basis for implementing programs and interventions to address problems with teachers’ organizational commitment. Novelty: Previous studies have only focused on some variables that influence organizational commitment, such as remoteness, emotional exhaustion, inaccessibility of healthy and sufficient school accommodations, and lack of local community linkages without a clear theoretical framework. Fortunately, this study explored other relevant factors, such as leadership and the school environment, as predictors of organizational commitment by establishing related theories to strongly support these variables with corresponding indicators.